#TITLE_ALTERNATIVE# - (NIM 15104061); Pembimbing: Dr. Ir. Eka Djunarsjah, M.T., dan Sofan Prihadi, ST. , JUMADI
Flood as the impact of the rising of the sea levcl, is a common problem that always exists around coastal areas. The sea level rise is generally influenced by global warming. furthermore, natural disasters such as storm wave, land subsidence, as well as high tide, have also given a contribution to the sea level rise. The sea level rise will cause such a great impact, either local or national scale. Therefore, it is needed to have a way to do modeling and stimulation of the impact of the sea level rise. One of ways that can be used is by three dimensional (3D) modeling and stimulation. Information in the form of three dimensions, can be achieved by Airborne Laser Scanning (ALS) technology that can produces depth and detail topography of coastal areas quickly in fast and accurately. Nations like: American, Canada, and Swedia names ALS technology by the name of LIDAR (Light Detecting and Ranging). Based on the measured object LIDAR is divided into two. One is, LIDAR for depth measurement [Airborne Laser Hydrography (ALH) or Airborne Laser Bathymetry (ALB)]. Another is LIDAR for topographic measurement of the land surface [Airborne Altimetric LIDAR]. Applying this technology, is useful to assist the nearest institution in handling the flood. Furthermore, it can be used in planning the space formation system and natural disasters mitigation.